Acceptance of artificial nesting sites by pollinating mason bees in commercial fruit plantations (Hymenoptera, Megachilidae: mixed Osmia cornuta and O. rufa population) - Benedek, P.; Nyéki, J.; Soltész, M.; Szabó, T.; Konrádné, C. (International Journal of Horticultural Science, 2010)
During a four yeas long experiment a simple bee shelterswas found to be a propermethod to increase the size ofmixed natural populations of the early season Osmia cornuta and O. rufa under practical farm conditions. Instead of the number of pesticide applications the earliness of the flowering of the fruit species in the orchards was found to be themost important factor in the rate of acceptance of reed as nestingmediumby Osmias in the bee shelter. This relationship was negative and highly significant (r = –0.829, p